Individualized Diets in Patients with Kidney Disease and Kidney Transplants: A Narrative Review - Lilio Hu; Greta Borelli; Elisa Gessaroli; Chiara Ruotolo; Sofia Bin; Giuliana Papalia; Gemma Patella; Maria Elena Liberti; Olga Baraldi; Gianluigi Zaza; Irene Capelli; Michele Provenzano (Life)
Chronic kidney disease (CKD) is a widespread condition with significant cardiovascular risks and a progression to end-stage kidney failure. In recent years, increasing attention has been paid to the role of dietary interventions as a factor capable of influencing disease trajectory. This review summarizes the current observational and interventional evidence on various dietary approaches in patients with CKD and kidney transplants (KTs), including Mediterranean, plant-based, and low-protein diets. A balanced Mediterranean diet, rich in fruits, vegetables, whole grains, fish, and unsaturated fats, shows promises in improving the prognosis for CKD patients. Plant-based diets, which emphasize legumes, vegetables, and grains while minimizing animal protein, improve blood pressure and the glycemic and lipid control. Low-protein diets (LPDs), typically providing less than 0.6 g/kg/day of protein, may reduce the CKD progression and nitrogen burden, further delaying the initiation of dialysis. In conclusion, diets represent a valuable and underutilized therapeutic strategy in the management of CKD and KTs, influencing disease progression and patient outcomes.